A VALUABLE MEDICINAL PLANT - Xalimova Moxigul Rustamovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
Peganum harmala L. (Syrian Rue) is a perennial herbaceous plant of the family Nitrariaceae, widely distributed in arid and semi-arid regions of Eurasia and North Africa. This plant has been traditionally used in folk medicine across many cultures due to its pronounced bioactive properties. This article provides a comprehensive overview of the biological and ecological characteristics of P. harmala, as well as an in-depth analysis of its medicinal properties, attributed to its rich phytochemical composition, particularly the presence of β-carboline alkaloids. The chemical composition, pharmacological action, traditional uses, and potential for modern pharmacology are discussed.